Pengaruh Beban Kerja Dan Fasilitas Kerja Terhadap Efektivitas Pelayanan Karyawan Pada Divisi Pengendalian Pelayanan Navigasi Penerbangan LPPNPI Di Jakarta - Hidayat, Rahmad; Rofiyanti, Eka; Utami, Windi (JAMBIS : Jurnal Administrasi Bisnis, 2024)
This study aims to determine and analyze the effect of workload and work facilities on the effectiveness of employee services at the LPPNPI Aviation Navigation Service Control division in Jakarta. The background of this research is that the services provided by LPPNPI have not been evenly distributed. Indonesia, which consists of many islands, has remote areas that still do not have good internet access, and there are even areas that do not have internet access at all. As a result, employees in the Aviation Navigation Service Control Division are unable or difficult to send flight news. Meanwhile, the SMS Gateway planning that has been initiated in recent years has not yet been fully realized by the company. Respondents in this study were employees of the Aviation Navigation Service Control Division, totaling 60 people. This research was conducted at Perum LPPNPI for a period of 5 months, starting from November 2021 to March 2022. The results of this study are that there is a significant effect between the Workload variable on the Employee Service Effectiveness variable of 48.7%, there is a significant effect between the Work Facilities variable and the Employee Service Effectiveness variable of 41.4%, there is a positive and significant effect of Workload and Work Facilities together on the Employee Service Effectiveness of the LPPNPI Aviation Navigation Service Control Division in Jakarta by 53.3%.